2017
DOI: 10.1080/03630269.2017.1302467
|View full text |Cite
|
Sign up to set email alerts
|

Hb Bakersfield (HBA1: c.151_152insGGAGCC): The Insertion of Arg-His Between Codons 49 and 50 of the α1-Globin Chain Leads to Increased Oxygen Affinity

Abstract: We describe an insertion variant on the α1-globin gene (HBA1) identified in a 49-year-old woman of Jurassian ancestry presenting with macrocytosis and erythrocytosis. The variant resulted in a peak of 15.5% of the total hemoglobin (Hb) on high performance liquid chromatography (HPLC). Stability and oxygen affinity testing revealed that the variant was stable and had an increased oxygen affinity. Molecular genetic testing detected the heterozygous sequence variant Hb Bakersfield [α50(CE8)His→0; Arg-Ser-His- ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In addition, it was found that higher MCV was associated with an elevated oxygen pressure ( 27 ) and an increased oxygen affinity in red blood cells ( 28 ). Then higher MCV could result in enhanced oxygen saturation in red blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was found that higher MCV was associated with an elevated oxygen pressure ( 27 ) and an increased oxygen affinity in red blood cells ( 28 ). Then higher MCV could result in enhanced oxygen saturation in red blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer RBCs will result in less oxygen available to the tumor, which will increase the proportion of hypoxic tumor cells. Hypoxia reduces the sensitivity of cells to radiation therapy, leading to a poor prognosis (21,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant correlation between MCV and several oxygen parameters [ 11 ]. Higher MCV are associated with an elevated oxygen pressure [ 11 ] and an increased oxygen affinity in red blood cells [ 12 ]. And then higher MCV leads to enhanced oxygen saturation in red blood cells.…”
Section: Discussionmentioning
confidence: 99%